Low-quality employment trajectories and mental health disorders among Swedish and migrant workers: Roxana Pollack. (25th October 2022) - Pollack, R; Kreshpaj, B; Jonsson, J; Bodin, T; Gunn, V; Orellana, C; Östergren, P; Muntaner, C; Matilla-Santander, N
Abstract: Aim: This study aims to examine the effects of low-quality employment trajectories on severe common mental disorders (CMD) according to Swedish and foreign background. Methods: This is a longitudinal study based on Swedish population registries (N = 2, 703, 687). Low- and high-quality employment trajectories observed across five years (2005-2009) are the exposure with severe CMD as outcome (2010-2017). Adjusted hazard ratios (HR) were calculated using Cox regression stratified according to background (first-generation (i) EU migrants, (ii) non-EU migrants, (iii) second-generation migrants, (iv) Swedish-born with Swedish background) and sex. The reference group were Swedish-born with Swedish background in a Constant high-quality employment trajectory. Results: Second-generation migrants had an increased risk of CMD compared to Swedish-born with Swedish background when following low-quality employment trajectories (e.g., male in Constant low-quality HR: 1.53, 95% CI: 1.41-1.68). Female migrant workers, especially first-generation from non-Western countries in low-quality employment trajectories (e.g., Constant low-quality HR: 1.65, 95% CI:1.46 - 1.87), had a higher risk of CMD compared to female Swedish-born with Swedish background. The confidence interval for CMD risk showed little differences between migrant groups (1st and 2nd generation) compared to the reference group. Conclusions: Low-quality employment trajectories appear to be determinants of risk for CMD, having a differential impact according to background of origin and sex. We observe a higher risk for severe CMD across migrant groups, especially second-generation migrants, compared to Swedish-born with Swedish background. Further qualitative research is recommended to understand the mechanism behind the differential mental health impact of low-quality employment trajectories according to foreign background. Key messages:  First and second-generation migrants in low quality employment have higher risk of severe common mental disorders compared to Swedish born with Swedish background workers in low quality employment.  Policies targeting working conditions in low-quality employment and promoting workers mental well-being are essential to reduce this higher risk for developing CMD, especially for migrant populations.